Curriculum Evaluation of Study Program of Christian Religious Colleges - Oci, Markus; Roesmijati, Roesmijati; Telaumbanua, Arozatulo; Haniko, Paulus; Pane, Ridwan Tonny Hasiholan (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Evaluation is part of the management system, namely planning, organization, implementation, monitoring and evaluation. The curriculum is also designed from the planning, organization, implementation and finally monitoring and evaluation stages. Evaluation of the Christian Religious College Study Program curriculum is a set of plans and arrangements regarding the content as well as study materials and lessons as well as ways of delivering and assessing them which are used as guidelines for organizing teaching and learning activities at Christian Religious Colleges (PTKK). The research method used by the author is a descriptive method whose purpose is to describe or make a description of what is being investigated and with an insight approach. The results of the evaluation of the Christian Religious College Study Program curriculum focus on the application or implementation of the curriculum, namely: determining the profile of graduates, graduate learning outcomes, study materials, forming courses, grouping courses, determining course structures, semester learning plans.